The Role of Preschool Educational Institution Psychologists in the Psychological Preparation of Children for School and Innovative Approaches - Mominova Khijran Eldar kizi (International Journal of Formal Education, 2025)
This article analyzes the role of preschool educational institution psychologists in the psychological preparation of children for school and explores innovative approaches. It highlights the significance of psychological factors in school readiness, including key aspects of cognitive, socio-emotional, and motivational development. Additionally, the article examines the role of psychologists in diagnostics, psychocorrection, and adaptation processes. The effectiveness of modern psychological methods, including play therapy, art therapy, TRIZ pedagogy, and sensory integration techniques, in facilitating children's school adaptation is also studied. The article is aimed at developing practical recommendations for preschool psychologists, educators, and researchers.